The “Big Five” Phytochemicals Targeting Cancer Stem Cells: Curcumin, EGCG, Sulforaphane, Resveratrol and Genistein - Naujokat, Cord; McKee, Dwight L. (Current Medicinal Chemistry, 2021)
Cancer stem cells (CSCs) constitute a subpopulation of tumor cells that possess self-renewal and tumor initiation capacity, and the ability to give rise to the heterogeneous lineages of cancer cells that comprise the tumor. CSCs exhibit intrinsic mechanisms of resistance to virtually all conventional cancer therapeutics, allowing them to survive current cancer therapies and to initiate tumor recurrence and metastasis. Different pathways and mechanisms that confer resistance and survival of CSCs, including activation of the Wnt/β- catenin, Sonic Hedgehog, Notch, PI3K/Akt/mTOR and STAT3 signaling pathways, expression of aldehyde dehydrogenase 1 (ALDH1) and oncogenic microRNAs, and acquisition of epithelial-mesenchymal transition (EMT), have been identified recently. Certain phytochemicals, in particular curcumin, epigallocatechin-3-gallate (EGCG), sulforaphane, resveratrol and genistein have been shown to interfere with these intrinsic CSC pathways in vitro and in human xenograft mice, leading to elimination of CSCs. Moreover, recent clinical trials have demonstrated the therapeutic efficacy of five phytochemicals, alone or in combination with modern cancer therapeutics, and in various types of cancer. Since current cancer therapies fail to eradicate CSCs, leading to cancer recurrence and progression, targeting of CSCs with phytochemicals such as curcumin, EGCG, sulforaphane, resveratrol and genistein, combined with each other and/or in combination with conventional cytotoxic drugs and novel cancer therapeutics, may offer a novel therapeutic strategy against cancer.
Keywords: Curcumin